Benzene and leukemia: from scientific evidence to regulations. A historical example - Belingheri, Michael; Fustinoni, Silvia; De Vito, Giovanni; Porro, Alessandro; Riva, Michele Augusto (La Medicina del Lavoro, 2019)
Background: Benzene is a highly flammable, highly volatile liquid aromatic hydrocarbon. It has been used in many industrial processes as a solvent or a starting material. At the beginning of the twentieth century, it was very widely used in the workplace, especially in printing and in the shoe manufacturing and rubber industries. Although benzene was first recognized to cause aplastic anemia, its association with leukemia has been investigated only since the 1930s. In 1963, Italy was one of the first countries in the world to adopt a law to ban benzene as a solvent in work activities. Objectives: This study analyzed the contribution of the Clinica del Lavoro in Milan, Italy, to studies of the relationship between exposure to benzene and leukemia. Methods: Scientific literature and historical sources on benzene and leukemia in the twentieth century were reviewed, and interviews with a first-hand witness of that period were conducted. Results: By 1928, several scholars had reported anecdotal cases of leukemia among workers exposed to benzene. Enrico Vigliani was the first to collect all of these cases and to try to conduct statistical analysis on these data, in order to support the association between benzene and leukemia. In the 1960s, Vigliani and Alessandra Forni showed that benzene could cause chromosome aberrations in the bone marrow that could produce leukemic clones. Conclusions: As a result of these studies and the subsequent regulations which banned benzene, exposure conditions changed in the workplace in the last few decades. The resulting low concentrations have prompted researchers to investigate new exposure biomarkers and to study any related health problems.